INOVASI BUS RAPID TRANSIT TERHADAP KEPUASAN MASYARAKAN PADA TRANSPORTASI PUBLIK DI KOTA TANGERANG - Septiaty, Euis; Asusti, Dea Indah Tri; Runingsah, Indah; Fadli, Yusuf (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
The mobility of urban citizens is demonstrated through a transportation system supported by adequate transportation policies and networks. The Tangerang City Government strives to realize this commitment through Bus Rapid Transit (BRT)-based transportation that is sustainable and oriented towards the development of modern cities. The purpose of the study was to see whether transportation mobility in BRT Tangerang City has a relationship with community satisfaction of service users. This study uses a quantitative approach that analyzes two variables, namely urban transportation mobility and community satisfaction. The sampling used a multistage random sampling technique and involved 100 respondents. The results showed that urban transportation mobility has not had a significant impact on community satisfaction, where the results of the t test explain The hypothesis carried out in this study is not appropriate because the calculated t value is smaller than the table t (-0.648 > 0.195). This means that H0 (There is no effect of SUM on community satisfaction in using BRT) is accepted and H1 (there is an effect of SUM on community satisfaction in using BRT) is rejected because variable (x) SUM negatively affects variable (y) community satisfaction which has a value of 0.4% and 99.6% is affected by other variables.